(untitled) (Research, Society and Development, 2021)
This article aims to contribute to the debate about Higher Education in indigenous teacher training from the perspective of interculturality in Brazil, as a project of resistance to the Eurocentric colonialist model, aiming at the construction of an epistemology that dialogues with indigenous peoples in their diversity in the Latin American, Pan-Amazonian and Brazilian context. This is a bibliographical and documental study with a quantitative-qualitative approach as its methodological basis. The results indicate that indigenous Higher Education in the Brazilian territory is the result of historical struggles in the field of public policies for recognition and rights, has contributed to the reaffirmation of ethnic identities and the continuous dialogue between local and universal knowledge in teacher training. However, there are still many obstacles to the implementation of an intercultural indigenous teacher education, as interculturality has not always been able to deal with the complexity of thinking about teacher education that is strongly marked by the colonialist model and by hegemonic neoliberal ideologies. However, based on these reflections, we emphasize that the socio-historical moment requires strengthening the struggle of indigenous peoples in the construction of a differentiated, intercultural and bilingual higher education in the face of the setbacks imposed by the current government policy.